How Do Pancasila Economics and Islamic Economics Relate to Financial Governance Policies in Indonesia? - Syarah Siti Supriyanti; Dwi Nofiana Gita Pertiwi (IAIN Syekh Nurjati Cirebon, 2025)
Pancasila economics is an institutional economic system that upholds the core values of Pancasila as Indonesia’s state ideology. Its five principles—ethics, humanity, nationalism, democracy, and social justice—serve as fundamental references for economic models in Indonesia. Meanwhile, the Islamic economic system is based on the teachings and values of Islam, derived from the Qur'an, As-Sunnah, ijma, and qiyas. This study aims to analyze the synchronization between Pancasila economics and Islamic economics in relation to various government policies, particularly in response to the challenges posed by global capital and liberalism. This research employs a qualitative approach (literature review) by analyzing relevant theories from books, journals, and online media. The Islamic economic system, rooted in the Qur'an and As-Sunnah, serves as a religious framework for Muslim communities, while Pancasila economics is the officially recognized economic system of Indonesia, founded on the principles of the state ideology. Both economic models share a strong social and moral vision, emphasizing economic equality and social justice. The findings reveal that when juxtaposed, Islamic economics and Pancasila economics converge in their ultimate goal of achieving welfare and justice for all members of society.